Afghanistan Development Update, January 2020 : Navigating a Sea of Uncertainty - World Bank (World Bank, Washington, DC, 2020)
Afghanistan currently faces a sea of uncertainty. Outcomes of the September 2019 presidential elections are not yet known, and preliminary results have been challenged. Insecurity continues, with government and insurgent operations imposing an increasing burden in terms of civilian casualties. Negotiations between the US and the Taliban have recently resumed, but prospects for and the contents of any eventual political settlement remain unclear. In the meantime, the duration and extent of continued international security support is being questioned. While international grants continue to finance 75 percent of public expenditure, current aid pledges expire at the end of 2020, with some major donors signaling intentions to significantly reduce support. This context of uncertainty has fundamental implications for the economy, with growth and investment constrained by weak confidence.